Penerapan Media Pembelajaran Slow Motion Terhadap Hasil Belajar Roll Depan - Irma Febriyanti (Universitas Nahdlatul Ulama Cirebon, 2023)
The world of education is not far from teaching and learning activities. Educators play an important role in the success of the learning process. The use of learning media has a role during the learning process. The use of appropriate media can improve student learning outcomes. This study aims to determine the effect of slow motion learning media on forward roll learning outcomes. This research is a quantitative descriptive research in the form of a quasi-experimental. The population in this study is all classes of V at SDN Balonggabus with the sample used, namely 31 students. This research will be conducted 4 times. The data collection technique used is the learning achievement test instrument. The analysis technique used is descriptive, normality test, and hypothesis testing to prove the influence of learning media on student learning outcomes. Based on the results of the analysis, the results show that there is influence as evidenced by the results of the hypothesis test of 0.00, which means <0.05. So it can be concluded that there is a significant influence of the application of slow motion learning media on learning outcomes of forward roll.